Distribution, ecology and conservation of the Andean Flamingo (Phoenicoparrus andinus Philippi, 1854) (Aves: Phoenicopteriformes): A systematic review about its status in Peru. - Ortiz, Enver Pastor (2023)
We present information on the status of the Andean Flamingo (Phonicoparrus andinus Philippi, 1854), based on a thorough literature review, access to databases, and field observations. We address aspects of the distribution, habitat, population, movements, diet, threats, and conservation status of this rare species. We confirm its presence in thesouthern Andes of Peru with sporadic sightings on the coast. The main habitats are the puna and high Andean salt flats, and in some cases, wetlands located in lower lands that are influenced by the rapid fluctuations of water resources. The population recorded since 1997 seems to be stable in summer; but with eventual fluctuations of thousands of flamingos during winter. Their movements towards Peruvian territory are from their breeding sites in Chile and Bolivia, without any relation to any migratory pattern, seasonality, or the age of the birds and with habitat preference. In one of its main congregation sites, recent information on potential food items has been found, suggesting that the presence of the species is due to their availability and quality. The Andean Flamingo is threatened mainly by habitat modification due to human activities related to the use of water resources. Finally, the state of its conservation and the efforts made, are still insufficient and require greater and special attention to preserve the species and its main habitats in Peru.